(untitled) (Research, Society and Development, 2020)
The aim of this study was to investigated factors associated with the functional impairment of older adult patients with type 2 diabetes mellitus (type 2 DM) and identify the influence of sociodemographic, clinical, and functional factors in this population. This is an observational analytical, and cross-sectional study, which evaluated 159 individuals of both genders, aged 60 years or older. The WHODAS (World Health Organization Disability Assessment Schedule) total score was analyzed in relation to other variables of the study, using the following statistical tests: Mann-Whitney, Kruskal-Wallis, Dunn’s post hoc, Spearman correlation, and simple linear regression analysis. Significance level was set at 5% (p<0.05). In total, 12 linear regression models were generated and the latter was selected for elaborating the prediction equation and its possible interpretations. Functional impairment was associated with sociodemographic, clinical, and functional factors. Sedentary lifestyle, overweight, cognitive deficit, decreased mobility, and falls were the factors that predicted the restriction of functional performance in older adults with type 2 DM. This study assessed the relationship between sociodemographic, clinical, and functional factors concerning the functional impairment of older adults with type 2 DM, reaffirming that this disease causes negative impacts in a global way and that the association among these factors leads to a decrease in functionality and worsening of life quality in this population. The findings of this study point out the importance of preventive programs in order to promote behavioral changes that can reduce the impact of type 2 DM complications.